The tumor microenvironment of hepatocellular carcinoma and its targeting strategy by CAR-T cell immunotherapy - Guizhen, Zhang; Guanchang, Ji; Liwen, Liu; Huifen, Wang; Zhigang, Ren; Ranran, Sun; Zujiang, Yu (Frontiers in Endocrinology, 2022)
Hepatocellular carcinoma (HCC) is the most prevalent subtype of liver cancer, which currently ranks sixth in incidence rate and third in mortality rate of all cancers. Despite great advances in systemic therapy, such as molecular-targeted agents, HCC has one of the worst prognoses due to drug resistance and frequent recurrence and metastasis. Increasing evidence suggests that the tumor immune microenvironment (TME) plays an important role in the progression and treatment of HCC. Adoptive immunotherapy leveraging chimeric antigen receptor-modified T (CAR-T) cells holds great promise for the treatment of cancer. However, in the face of a hostile TME, the anti-tumor efficacy of CAR-T cells will also be greatly compromised. In this review, we provide an overview of TME features in HCC, discuss recent advances and challenges of CAR-T immunotherapy in HCC.